Profitabilitas Perbankan Syariah - Ismawati, Kun; ., Nurhayati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2014)
This study aimed to analyze the effect of size, Total Equity to Total Assets, Total Loans to Total Assets, Total Deposits to Total Assets on ROA(Return on Assets) on Bank Syariah In Indonesia. Purposive sampling method used in this research study. There were two syariah banks in this research. The research samples werein the form ofsecondary data. The data was listed in the Indonesia Stock Exchange during period 2009-2013. The statistical method used to test the hypothesis in this study was multiple regression. The results of the data analysis obtained in this study were: 1) Size has a positive but not significant effect to the profitability of Syaria banks 2) Total Equity To Total Assets (TE / TA) has a positive but notÂ  significant effect on profitability. 3) Total Loans to Total Assets (TL / TA) has a negative but not significant effect on profitability. 4) Total Deposits To Total Assets (TD / TA) has a positive but not significant effect on profitability.Keyword: Size, total equity to total assets, total loans to total assets, total deposits to total assets, ROA